PENGARUH MOTIVASI DAN KOMPETENSI KARYAWAN TERHADAP KINERJA KARYAWAN DI KECAMATAN KEMIRI TANGERANG - Rizka Akbar, Irfan; Suryadi (Journal of Research and Publication Innovation, 2023)
This research aims to determine the Influence of Employee Motivation and Competence on Employee Performance in the Kemiri District, Tangerang Regency. The research method used is quantitative, employing a saturated sample technique, and the data is processed using SPSS 26. The results of the analysis indicate that motivation has a positive and significant influence on employee performance, with a calculated tvalue of 2.824, which is greater than the tabulated tvalue of 2.000, and a Sig. Prob. of 0.006, which is less than 0.05. Similarly, competence also has a positive and significant influence on employee performance, with a calculated tvalue of 4.334, surpassing the tabulated tvalue of 2.000, and a Sig. Prob. of 0.000, much smaller than 0.05. Furthermore, this research also demonstrates that motivation and competence together have a significant influence on employee performance, with an Fvalue of 150.739, significantly greater than the tabulated Fvalue of 3.15, and a Sig. Prob. of 0.000, much smaller than 0.05. The combined contribution of motivation and competence to employee performance is 83.6%, while the remaining 16.4% is influenced by other factors outside the scope of this study.